SISTEM INFORMASI E-RAPOR BERBASIS WEB (STUDI KASUS : TK ISLAM AL IKHLAS SERPONG) - Imroni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The implementation of electronic report card policies in the 2013 curriculum is an alternative solution to educational problems. Many obstacles are faced due to various factors that often influence policy implementation. Policies that have passed the stages are not necessarily successful in their implementation. TK ISLAM AL IKHLAS SERPONG is a children's education school/kindergarten which consists of TK A, TK B, and KOBER. This application also cannot be used by students because students are not given access or permission to view their own grades. For this reason, a report card application is needed that can improve services to students quickly in terms of getting grades while making it easier for teachers to fill in report cards.